Box-Behnken Design-Desirability Function Approach in Optimization of HPLC Method for Simultaneous Determination of Ibuprofen Along with Additives in Syrup Formulation - Dinc-Zor, Sule; Donmez, Ozlem Aksu (OXFORD UNIV PRESS INC, 2021)
Background: The advantages of simultaneous analyses are a decrease in analysis time and a more economical use of solvents and reagents. It is desirable that HPLC analyses possess both short term and good resolution. Objective: The aim of the current study is to develop an HPLC method for the simultaneous determination of ibuprofen, sodium benzoate, methyl paraben and propyl paraben as preservatives, and sunset yellow as a colorant, in syrup formulation. Method: To optimize chromatographic separation conditions, multi-response optimization using the Derringer's desirability function was employed for the development of a rapid and efficient HPLC method. The ranges of independent variables used for the optimization process were 50-60% (v/v) for acetonitrile, 5.0-7.0 for pH, and 1.0-2.0 mL/min for flow rate of the mobile phase. The effects of these variables on the output responses, such as critical resolution between sunset yellow and sodium benzoate and retention time of the last peak indicating analysis time of the method, were evaluated by statistical experimental design. Results: Optimum conditions fixed for the simultaneous analyses were acetonitrile:phosphate buffer (60:40, v/v), pH 5.0, and a flow rate of 1.8 mL/min. The eluate was monitored using a photo diode detector set at 220 nm. Total chromatographic analysis time was approximately 3 min. Conclusions: The developed method validated as per International Conference on Harmonization guidelines was successfully applied for the determination of five compounds in their pharmaceutical formulation.
Keywords: PHARMACEUTICAL FORMULATIONS; FOOD; Chemistry; Food Science & Technology